CALIBRATION OF HDM-4 FOR USE IN PAVEMENT MANAGEMENT SYSTEMS (PMS) - Mushule, N K (Tanzania Journal of Engineering and Technology, 2017)
One of major problems of road management in developing countries is the lack of decision making tools for preparing road maintenance programmes. This results in poor resource allocation and poor utilisation of existing assets. Pavement management systems (PMS) have been developed around the world in order to assist with the pavement management process in a co-ordinated and systematic manner. Some developed countries have derived pavement performance models that are suited to local conditions by setting up long term pavement performance studies. Conversely, most developing countries do not have the resources required to set up similar large-scale field experiments. However, validation and calibration of models developed from comprehensive studies elsewhere offers a viable alternative for such countries. This paper evaluates the feasibility of using HDM-4 as a support software and determines level 1 calibration factors for PMS in Tanzania. The paper demonstrates the use of a calibrated HDM-4 to determine the required road management information in developing countries.